Ableism differs by disability, gender and social context: Evidence from vignette experiments - Shane Timmons; Frances McGinnity; Eamonn Carroll (The Economic and Social Research Institute (ESRI), 2023)
Existing research on ableism has conceptualised it as a general attitude, rather than one that can manifest differently depending on the nature of the disability, the disabled person's gender and the social context. Our aim was to investigate variation in attitudes to disability depending on these factors. A nationally representative sample of 2,000 adults read a series of vignettes about issues faced by disabled people, relating to education, employment, de-institutionalisation, relationships and welfare payments. Vignettes varied by presence and type of disability and the protagonist's gender. Some vignettes asked participants whether it was acceptable to treat a disabled person in a specific way (e.g., not hire them for a job) and others asked whether it was acceptable for a disabled person to act in a certain way (e.g., to engage in a romantic relationship). The study was pre-registered and has open materials, data and analysis code. Judgements about how a disabled person was treated showed clear evidence of ableism towards some disabilities (e.g., autism, mental health issues) but not others (e.g., a spine disorder). Judgements about the actions of a disabled person were more nuanced. A disability-gender intersectionality effect was observed for judgements about romantic relationships, with physically disabled women penalised compared to men but no such difference observed for intellectual disability. No intersectionality or ableism was observed on a vignette about refusing poorly paid work. Having a close relationship with someone who has a disability predicted more positive attitudes across social contexts. We find clear evidence that ableism manifests differently depending on the nature of the individual's disability, their gender and the social context, questioning the previous conceptualisation of ableism as a general attitude. There is considerable scope for further research investigating the forms ableism can take and the conditions that elicit it.
Keywords: 330; ableism; disability; mental health; stigma; discrimination; gender; experiment; stereotype content model